The effect of cutting technique on the mortality and resprouting vigor of poplar stumps in short-rotation plantations - Spinelli, Raffaele; Magagnotti, Natascia; Lombardini, Carolina; Leonello, Elaine Cristina [UNESP] (Canadian Science Publishing, 2021)
Mechanical felling is the most cost-effective solution for harvesting short-rotation poplar plantations, but the damage inflicted by conventional shear-cutting devices on tree stumps has raised concerns about stump mortality and resprouting vigor, both of which are crucial to coppice regeneration. To determine whether such concerns are justified, this experiment monitored the survival and resprouting vigor of 11 sample blocks composed of two 10-stump row segments that were cut according to one of two methods: (1) a chainsaw or (2) an excavator-mounted shear. The sample blocks were located within the same plantation, established 7 years earlier with hybrid poplars (Populus nigra x Populus deltoides) belonging to the AF8 clone. One year after cutting, no differences were found between treatments in terms of stump mortality, number of shoots per stump, shoot diameter at 30 cm from the insertion, or shoot height. These results support the use of mechanical shears to fell short-rotation poplar coppice. However, further studies should be conducted on multiple fields and clones in order to safely generalize these preliminary findings.
Keywords: felling; regeneration; growth; plantation